In vitro Release Kinetic Study of Theophylline from Kollidon SR Polymer Based Matrix Tablet - Kabir, Abul Kalam Lutful; Halder, Shimul; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Controlled release tablet matrix of theophylline was prepared with kollidon SR, a spray dried powder grade polymer (polyvinyl acetate and povidone based matrix rate retarding hydrophobic materials) by utilizing direct compression technique. Different proportion of kollidon SR was used to develop the matrix builder in the five proposed formulations (F-1 to F-5) for the study of release rate retardant effect at 10, 12, 15, 18 and 21% of total weight of matrix tablet, respectively. The in vitro dissolution study of the matrices of those proposed tablet formulations were carried out in simulated gastric medium (pH 1.3) for first two hours and then in simulated intestinal medium (pH 6.8) for 6 hours using USP dissolution apparatus II (paddle method). The formulation F-3 (using 15% polymer) and F-4 (using 18 % polymer) met the optimum release profiles of active ingredient for 8 hr period of total study. The release kinetics for theophylline was plotted against zero order, first order and Higuchi release rate kinetics to evaluate the release mechanism of drug from the formulated tablet matrix. The release kinetics of formulation F-3 and F-4 was followed very closely by Higuchi release rate kinetic order than other kinetics such as zero order and first order kinetics which has been reflected the type of drug release from the tablet matrix by diffusion as well as erosion mechanism. Dhaka Univ. J. Pharm. Sci. 14(1): 43-48, 2015 (June)